2012
DOI: 10.1177/0009922812443731
|View full text |Cite
|
Sign up to set email alerts
|

In-Office Influenza Vaccination by US Pediatric Providers Varies Greatly and Is Higher Among Smaller Offices

Abstract: During the 2010-2011 US influenza season, 105 pediatric and 13 family practice offices participated in a prospective observational study of in-office influenza vaccination of children. Office characteristics, influenza vaccinations, and vaccination-related activities were reported. Among pediatric offices, first dose vaccination rates (2% to 60%), 2-dose compliance (11% to 100%), the duration of vaccine availability (60-302 days), and office visit type (well vs sick vs clinic) used for vaccinations varied grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The effect of age on vaccination rates seems to be consistent across studies including the present study, with younger children more likely to be vaccinated than older children [3, 25, 28]. Medicaid-insured children have been reported as more likely to be vaccinated than privately insured or uninsured children at community health centers [29], but were less likely to be vaccinated in the present study, which included some community health centers and may be due to later delivery of VFC vaccines to Control sites.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The effect of age on vaccination rates seems to be consistent across studies including the present study, with younger children more likely to be vaccinated than older children [3, 25, 28]. Medicaid-insured children have been reported as more likely to be vaccinated than privately insured or uninsured children at community health centers [29], but were less likely to be vaccinated in the present study, which included some community health centers and may be due to later delivery of VFC vaccines to Control sites.…”
Section: Discussionsupporting
confidence: 69%
“…We speculate that practices with a high pre-intervention rate viewed themselves as already doing all that was feasible to vaccinate against influenza. Few studies have reported overall vaccination rates above 50%, with one observational study [25] reporting a maximum of 60% among 118 pediatric and family practices across the country. Thus, it may be difficult to achieve the 70% national goal by relying solely on primary care practices to vaccinate.…”
Section: Discussionmentioning
confidence: 99%
“…Little research has been performed on factors associated with 2-dose influenza vaccination compliance. In an earlier analysis of the 2010–2011 results from the current study, Toback et al [ 17 ] found that 2-dose compliance was higher in smaller offices and in offices with video reminder messages in waiting rooms. Other research among 6–23-month-old children found only visits between October and January related to increased levels of compliance [ 11 ].…”
Section: Discussionmentioning
confidence: 59%
“…One 30 found that paediatricians vaccinated children with intermittent asthma four times more often and children with severe asthma fourteen times more often than family doctors did. The other 31 study identified no differences between anti‐flu vaccination rates of healthy and high‐risk children when treated by family doctors or paediatricians.…”
Section: Discussionmentioning
confidence: 87%